THE EVOLUTION OF INTERNATIONAL LAW IN THE ASPECT OF WAR CRIMES AND CRIMES AGAINST HUMANITY - Abo Saeid, Tarek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2005)
The author of the publication considers the historical aspect of individual responsibility for crimes against humanity under international law, gives definitions of genocide and war crimes and points to factors which may contribute to increase the effectiveness in combating this type of crime.